Low Levels of Serum Paraoxonase Activities are Characteristic of Metabolic Syndrome and May Influence the Metabolic-Syndrome-Related Risk of Coronary Artery Disease. (22nd September 2011) - Martinelli, Nicola; Micaglio, Roberta; Consoli, Letizia; Guarini, Patrizia; Grison, Elisa; Pizzolo, Francesca; Friso, Simonetta; Trabetti, Elisabetta; Pignatti, Pier Franco; Corrocher, Roberto; Olivieri, Oliviero; Girelli, Domenico
Abstract : Low concentrations of plasma high-density lipoprotein (HDLs) are characteristic in metabolic syndrome (MS). The antioxidant ability of HDLs is, at least in part, attributable to pleiotropic serum paraoxonase (PON1). Different PON1 activities have been assessed in 293 subjects with (n = 88 ) or without MS (n = 205 ) and with (n = 195 ) or without (n = 98 ) angiographically proven coronary artery disease (CAD). MS subjects had low PON1 activities, with a progressively decreasing trend by increasing the number of MS abnormalities. The activity versus 7-O-diethyl phosphoryl, 3-cyano, 4-methyl, 7-hydroxycoumarin (DEPCyMC), which is considered a surrogate marker of PON1 concentration, showed the most significant association with MS, independently of both HDL and apolipoprotein A-I levels. Subjects with MS and low DEPCyMCase activity had the highest CAD risk (OR 4.34 with 95% CI 1.44–13.10), while no significant increase of risk was found among those with MS but high DEPCyMCase activity (OR 1.45 with 95% CI 0.47–4.46). Our results suggest that low PON1 concentrations are typical in MS and may modulate the MS-related risk of CAD.